Prevalence of oral cancer patients at the Pathology Anatomy Department RSUD Tasikmalaya year 2002-2007 - Dardjan, Murnisari (Universitas Padjadjaran, 2007)
Malignancy was included which happened in the oral cavity. Oral cavity cancer is statistically fever than other parts of a body but can to be dead. The incidence of malignancy was increased in the last 50 years throughout the world. The purpose of this research is to get distribution data about oral malignancy cases frequency at Rumah Sakit Umum Daerah/RSUD Tasikmalaya. Rumah Sakit Umum Daerah Tasikmalaya is a Referal Hospital from East Priangan region, West Java Indonesia. This is retrospective descriptive research. Samples were taken from Histopathologic form data patient at RSUD Tasikmalaya from January 2002-December 2007. The result of this study indicated that 15 cases oral malignancy cases from all samples 2943 histopathology specimen in the period. The most malignancy cases of carcinoma were squamous cell carcinoma (98%). Tongue became the most area in this cases which was 46.66%. Oral malignancy were common in men 54%. The group of ages 60-70% became the majority namely 40%. The conclusion of the research indicated that carcinoma cell squamous were became the greatest part of oral malignancy types.